DEVELOPING ENGLISH READING MATERIAL FOR THE ELEVENTH GRADE STUDENTS OF SOFTWARE ENGINEERING PROGRAM IN SMK NEGERI BINAAN PROVINSI SUMATERA UTARA MEDAN - Benedick Deo Agatha; Johan Sinulingga (Universitas Negeri Medan, 2018)
This study is aimed to design English Reading Material needed for students of Software Engineering Program and develop English Reading Material for Grade XI students of Software Engineering Program in SMK Negeri Binaan Provinsi Sumatera Utara Medan. This research was conducted by Research and Development (R & D) design through six stages; 1) Gathering Data and Information, 2) Analyzing data, 3) Designing new material, 4) Validated new material by the experts, 5) Revising reading material, 6) Final Project. The subject of this research was class XI-RPL 1 students of Software Engineering program consisting of 29 students. The instrumentations for collecting the data were questionnaire and interview. After , anlyzing the data, the researcher got the students’ needs. The data were gathered by administering interview and distributing the questionnaire to 29 respondents to get the students’needs. The interview and questionnaire results prove that the students need English reading materials which cointain English for Software Engineering program. Thus , developing English reading mateials were procedure text. Then , the procedure texts related to their study program. The products have been validated by experts. The average scores are 4,2 from English Lecturer and 4,3 from English Teacher.It means the developing materials categorized as relevant or appropriate for Grade XI Students of Software Engineering Program.